(untitled) (Jurnal iSpectrum, 2023)
Martial Art appears as a way for someone to defend or protect themselves and also as a performing arts. However, not all martial arts receive adequate facilities according to existing standards. Martial arts have been around for a long time and have developed over time. Ninjutsu is one of the ancient martial arts originating from Japan. Mie Prefecture is well known as a ninjutsu dojo and as the birthplace of the martial art itself. The development of this Ninjutsu martial arts has declined due to the lack of public interest. Some people see ninjutsu not as a sport or martial art. Based on this, the sensei (ninjutsu trainer) wants to change the negative stigma of society regarding Ninjutsu. This Ninjutsu has also entered Indonesia since it was introduced by Sensei Sanmoon Nakamura in 1994. Sensei Sanmoon Nakamura got this Ninjutsu martial art after graduating from Kevin Harthore Ninja School in Australia. He also created a platform called the Ninjutsu Indonesia Club (NIC), which has 30 branches in Indonesia. The purpose of this design is to provide education as well as a place for Ninjitsu practice according to predetermined standards, so that users will feel safe and comfortable during training and matches. The result of this design is an idea that is outlined in the design of the Dojo Ninjitsu which is located in Denpasar.